Myocardial infarction triggers Inflammatory deterioration of vascular niche by accelerating loss of a specific vessel subtype in bone. (25th November 2020) - Hoffmann, J; Luxan, G; Abplanalp, W.T; Rasper, T; Fischer, A.M; Muhly-Reinholz, M; Assmus, B; Zeiher, A.M; Dimmeler, S
Abstract: Introduction: The interface between heart and bone emerges as a key trigger of post-infarction inflammation and progression of chronic heart failure (CHF). However, our knowledge on the underlying mechanisms of this interaction is incomplete. Bone vasculature, specifically so-called H-type (Endomucinhigh) endothelial cells (EC), plays a crucial role in maintenance of the bone integrity and regulation of hematopoietic stem cells (HSC). While previous studies in mice showed the reduction of H-type vessels by aging, the impact of ischemic heart disease is unclear. Therefore, we aimed to investigate the effects of myocardial infarction (MI) and chronic heart failure on the vascular bone cell composition in mice and humans. Methods and results: Flow cytometric analysis of harvested bones at the different timepoints after MI induction in mice revealed a gradual loss of H-type endothelial cells in the time-course of developing chronic heart failure (P<0.05 at day 7 and 14 vs. control; P<0.0001 at day 28 vs. control). This results were confirmed in immunostainings of tibia sections showing a significant decrease of H-type vessel length after MI (p<0.05 at day 14 and 28, accordingly). The loss of type-H endothelium was accompanied by a significant expansion of long-term HSC in the bone (P=0.0005 at day 28 post MI vs. control). Importantly, type H ECs were also significantly reduced in the bone of ischemic post-infarct HF patients (n=16) compared with control subjects (n=8; P=0.0003). To gain insights into the mechanisms underlying the changes in the vascular niche, we performed single cells RNA sequencing of human BM ECs. These studies confirmed the decrease in Emcnexpressing ECs in ischemic HF patients, which was accompanied by significantly increased expression of inflammatory genes, including IL1b (P<0.0001). Inflammatory EC phenotypes and IL1b expression in HF could be further confirmed at protein level using cytospin immunostainings. Murine studies further revealed an early induction IL-1b specifically in H-type vessels already at day 1 after MI induction, which preceded the loss of H-type endothelium within the following 4 weeks. By inhibiting IL-1b production using a specific Nlrp3 inflammasome inhibitor (MCC950) we could observe a partial restoration of H-type EC frequencies (P=0.033) and a significant increase in H-type vessel length (p=0.035) at day 28 day after MI. Conclusions: Our data show for the first time an impact of myocardial infarction and chronic heart failure on the bone marrow vasculature. These changes seem to be strongly associated with inflammatory response in H-type vessels, which precedes its loss after MI. Specifically, the induction of the inflammatory cytokine IL1b may contribute to the disturbed phenotype. This suggest that inhibition of IL1b (e.g. by canakinumab) be used as a novel strategy to prevent or reverse the deterioration of the vascular bone function in ischemic heart disease. Funding Acknowledgement: Type of funding source: None